Thyroglossal Duct Remnant Carcinoma: Beyond the Sistrunk Procedure - Carter, Yvette (2014)
Thyroglossal duct remnants (TGDRs) account for more than 70% of anterior neck masses in children and 7% in adults; however, cancer is identified in only 1–2% of the cases. The diagnosis of a TGDR is based on clinical manifestation of a painless, anterior neck swelling, which elevates with swallowing. Cytological evaluation with fine needle aspiration and biopsy (FNAB) may facilitate the pre-operative diagnosis of malignancy, as the majority of TGDR cancers are of papillary histotype. The recommended treatment for symptomatic TGDR without evidence of malignancy is a Sistrunk procedure, which entails en bloc resection of the remnant and the mid-portion of the hyoid bone. The optimal management of patients with diagnosed malignancy is controversial, and in the past, additional total thyroidectomy was recommended for all of these patients. The purpose of this study is to review the literature on TGDR carcinomas, present the evidence on the available diagnostic tools, identify the surgical and post-operative medical management strategies, discuss current controversies, and conclude with a management algorithm.